Ankylosing spondylitis: A novel risk factor for atrial fibrillation — A nationwide population-based study. (15th January 2019) - Moon, Inki; Choi, Eue-Keun; Jung, Jin-Hyung; Han, Kyung-Do; Choi, You-Jung; Park, Jiesuck; Cho, Jun Hwan; Lee, Euijae; Choe, Wonseok; Lee, So-Ryoung; Cha, Myung-Jin; Lim, Woo-Hyun; et al.
Abstract: Background: Ankylosing spondylitis (AS) is a chronic inflammatory rheumatic disease, associated with a number of cardiovascular diseases. We sought to investigate whether AS increases the risk of atrial fibrillation (AF) in a nationwide population-based study. Methods: A total of 14, 129 patients newly diagnosed with AS (mean age 41.8 ± 15.3 years, 72% male) were recruited from the Korean National Health Insurance Service database between 2010 and 2014 and followed up for new onset AF. Age- and sex-matched non-AS subjects (1:5, n = 70, 645) were selected and compared with the AS patients. Results: During a mean follow-up of 3.5 years, AF was newly diagnosed in 486 patients (114 patients of the AS group). The AS patients developed AF more frequently than the non-AS subjects (2.32 vs. 1.51 per 1000 person-years). In multivariate Cox regression analysis, AS was an independent risk factor for AF (Hazard ratio [HR] 1.28, 95% confidence interval [1.03–1.58]). The AS with tumor necrosis factor inhibitor (TNFi) therapy group showed higher risk for AF (HR 1.60 [1.02–2.39]). In younger patients of the AS group (patients <40 years old), the risk for AF was three times higher than patients at same age in the non-AS group. AS was an independent risk factor for AF in men, but not in women (HR 1.53 [1.18–1.95]; HR 1.42 [0.94–2.08], respectively). Conclusions: AS was an independent risk factor for AF, especially in those under 40 years of age and those administered TNFi. It would be reasonable to screen for AF and stroke prevention in these high-risk patients. Highlights: Ankylosing spondylitis (AS) is an independent risk factor of atrial fibrillation (AF) in Asian population. Effect of AS on the risk of AF development is still significant after adjusted for other cardiovascular risk factors. Risk of AF development is greater in younger and male AS patients, and those treated with tumor necrosis factor inhibitor. Physician should be considered that AF screening is needed in these AS and high-risk patients.